Stability of Metal Oxide Semiconductor Gas Sensors: A Review - Chai, Hongfeng; Zheng, Zichen; Liu, Kewei; Xu, Jinyong; Wu, Kaidi; Luo, Yifan; Liao, Hanlin; Debliquy, Marc; Zhang, Chao (IEEE sensors journal, 2022)
Sensor stability is defined as the ability to maintain a relatively stable and repeatable signal over a sufficient period. Long-term stability for gas sensors is an essential capability for carrying out long-term data collection of human exhaled breath, environmental monitoring and other gas detection in the modern electronic information age. This article reviews the research advances on the stability of metal oxide semiconductor gas sensors in the past five years. The impact of structure, environment, toxicity and sensor array on the sensor stability are discussed. Then, the improvement schemes of existing materials and structure design are summarized. The achievements of structure doping, humidity, anti-poisoning and photoactivation are overviewed. Finally, the great significance of elucidating the sensing mechanism and carrying out the life acceleration test for future research and development is pointed out.